2021
DOI: 10.3390/v14010028
|View full text |Cite
|
Sign up to set email alerts
|

Selection for and Analysis of UV-Resistant Cryptophlebia Leucotreta Granulovirus-SA as a Biopesticide for Thaumatotibia leucotreta

Abstract: Cryptophlebia leucotreta granulovirus-SA (CrleGV-SA) is used as a commercial biopesticide for the false codling moth, Thaumatotibia leucotreta, in citrus and other crops. The virus is sensitive to UV irradiation from sunlight, which reduces its efficacy as a biopesticide in the field. We selected a UV-resistant CrleGV-SA isolate, with more than a thousand-fold improved virulence compared to the wild-type isolate, measured by comparing LC50 values. CrleGV-SA purified from infected T. leucotreta larvae was expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Furthermore, 18% of OBs showed no signs of UV degradation after 72 h exposure to UV irradiation. Consequently, virus populations may include individuals possessing a higher tolerance to UV irradiation that can be specifically selected for through serial passage after UV exposure [28,47], as was recently reported by us in a laboratory selection procedure from the same isolate of CrleGV-SA described in this paper [48].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, 18% of OBs showed no signs of UV degradation after 72 h exposure to UV irradiation. Consequently, virus populations may include individuals possessing a higher tolerance to UV irradiation that can be specifically selected for through serial passage after UV exposure [28,47], as was recently reported by us in a laboratory selection procedure from the same isolate of CrleGV-SA described in this paper [48].…”
Section: Discussionmentioning
confidence: 87%
“…This crystalline structure is formed by the OB protein granulin [33]. Whilst granulin protects the OB from harsh environmental conditions and enables the virus to persist for long periods of time in the soil or similar shaded environments, it has been shown that it cannot provide sufficient protection to the NC against UV irradiation to enable prolonged survival when exposed to sunlight [8,34].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is not recommended to utilise LdMNPV-45/0 in locations with high UV loads or at densities of forest stands. Another study reported the use of Cryptophlebia leucotreta granulovirus-SA (CrleGV-SA) as a commercial biopesticide against the false codling moth, Thaumatotibia leucotreta, in citrus and other crops (Mwanza et al 2022). This virus strain was isolated from infected T. leucotreta larvae and subjected to UV irradiation in a climate chamber with simulating field settings under laboratory condition.…”
Section: Selection Of Insect Baculovirus Resistant To Uv Irradiationmentioning
confidence: 99%
“…This virus strain was isolated from infected T. leucotreta larvae and subjected to UV irradiation in a climate chamber with simulating field settings under laboratory condition. This UV-resistant CrleGV-SA strain was thousand-fold more virulence than the wild-type isolate (Mwanza et al 2022). Single Nucleotide Polymorphisms (SNPs) was discovered in the 5 th generation of UV-resistant CrleGV-SA which is believed to have improved the UV tolerance and pathogenicity of the virus.…”
Section: Selection Of Insect Baculovirus Resistant To Uv Irradiationmentioning
confidence: 99%
“…24,25 Although studies have moved from artificial diet to more realistic scenarios involving host plants, either in laboratory-controlled conditions 16,26 or directly in the field, 27,28 they remain focused on a single plant species which limits our ability to generalise the outcome of pathogen interactions to different crop plants. Yet, host plants can directly affect entomopathogens and alter their persistence and viability on the plant 29,30 or indirectly affect them by changing insect behaviour. and thus pathogen acquisition, as well as susceptibility through changes in immunocompetence.…”
Section: Introductionmentioning
confidence: 99%